Akomudasi Pendidikan Lembaga Adat dalam mempertahankan tradisi Mamacah Cator Norbhuwat di desa Lobuk Bluto Sumenep - Fuadi, Ahmad; Abrianto, Danny; Fajriyah, Fajriyah; Sabariyah, Hayatun (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
The problem of the erosion of local community traditions, one of which is â€œmamacahâ€ tradition in Madura, which was identified from field data and facts, requires the participation of educational institutions, namely village customary institutions which should exist at the village level whose function is to provide education to the community about education to maintain arts and culture. . The Mamacah tradition has problems with various temporary factors, namely the development of the times and social change factors that affect the low interest of the younger generation as the successors of this tradition. This requires further study of how traditional institutions in the village accommodate village traditions through the steps of fostering the younger generation. The accommodation of the traditional institutions of Lobuk village is carried out by implementing â€œMamacahâ€ training education which is intensively taught to the young generation of the village with a convergence approach. By maintaining communication with village youth, Mamacah education can run harmoniously and continuously. The success of Lobuk village as the only independent village in Madura cannot be separated from the intensity of the education of the traditional institutions in it as a form of cultural capital for the knowledge of the young generation of the village and the symbolic capital of the establishment of educational institutions of traditional village institutions that continuously carry out arts and cultural education in the area including mamacah